The green tea polyphenolic catechin epigallocatechin gallate and neuroprotection. (2nd April 2020) - Khalatbary, Ali Reza; Khademi, Emad
Abstract : Epigallocatechin gallate is the most abundant composition of the tea catechins and is thought to be responsible for the majority of biological activity of green tea extracts such as antioxidant, anti-inflammatory, and antiapoptotic effects. Meanwhile, EGCG has been shown to be some of the neuroprotective effects against neural injuries and neurodegenerative diseases. This paper summarizes current knowledge on neuroprotective effects of EGCG and their molecular mechanisms responsible for the neuroprotection in various models of neurodegenerative and neural injury.